ANALISIS POTENSI PEMBANGKIT LISTRIK TENAGA PIKO HIDRO ARCHIMEDES SCREW TURBINE DI CURUG SAWER - Moch Rizky; Muchtar Ali Setyo yudono; Anang Suryana; Adi Nugraha (MEDIA ELEKTRIKA, 2023)
People all across the world depend on electricity, which is now primarily produced by fossil fuel power plants. The world is currently switching to use a sustainable and affordable energy source, new renewable energy, or NRE. Water is a energy source of NRE, making it one of the potential sources of NRE around the world. Sukabumi, which is spread out across a large region and has a lot of hydropower potential, has a great chance of being used to run Piko-scale hydropower. Curug Sawer, a popular tourist destination with the potential of hydro power plants, is one of the PHPP potentials in the Sukabumi region. Based on CaSimir and Simulink MATLAB simulations, this study presents an examination of the potential for a pico hydro power plant with an Archimedes Screw turbine. With an area discharge of 0.67 m3/s and a Head height of 1.1 m, the natural reservoir area at Curug Sawer served as the study's source of hydropower. With these parameters, this PHPP can generate 4.67 kW of electricity and 110 kWh of power each day. The tourism destination curug sawer area might save Rp 1,768,680.00 per month on power because of this possibility.